Medical and surgical management of the small pupil during cataract surgery. Issue 8 (August 2018) - Al‐Hashimi, Saba; Donaldson, Kendall; Davidson, Richard; Dhaliwal, Deepinder; Jackson, Mitchell; Kieval, Jeremy Z.; Patterson, Larry; Stonecipher, Karl; Hamilton, David R.
Abstract : N/A: As cataract surgery continues to evolve, the intraoperative small pupil continues to pose challenges to even the most experienced cataract surgeon. Several steps can be taken preoperatively to decrease the chance of intraoperative miosis. Even so, the problem of miosis during cataract surgery remains a relatively common occurrence. This paper discusses many steps, both preoperative and intraoperative, that can make surgery technically easier and safer, thus maximizing the postoperative outcomes and patient satisfaction. Complications associated with small‐pupil cataract surgery, risk factors for intraoperative miosis, the preoperative and intraoperative management of the small pupil during cataract surgery, and postoperative care are reviewed.